Predicting distributional shifts of commercially important seaweed species in the Subantarctic tip of South America under future environmental changes - Murcia, Silvia; Riul, Pablo; Mendez, Fabio; Rodriguez, Juan Pablo; Rosenfeld, Sebastian; Ojeda Villarroel, Jaime Andrés; Marambio Gallardo, Johanna Valeska; Mansilla Muñoz, Andres Omar (My University, 2020)
Shifts in species distributions are among the observed consequences of climate change, forcing species to follow suitable environmental conditions. Using species distribution models (SDMs), we aimed at predicting trends in habitat shifts of two seaweed species of commercial interest in the Subantarctic Patagonian region in response to ongoing environmental changes across temperate South America and worldwide. We gathered occurrence data from direct, on-site visual, and taxonomic identification (2009-2018) from global databases of species occurrence and from the scientific literature. We built the SDMs selecting putative predictors of biological relevance to Lessonia flavicans and Gigartina skottsbergii. We calibrated the SDMs using MaxEnt and GLMs for model evaluation, splitting our occurrence datasets into two parts: for model training and for model testing. The models were projected to future climate change scenarios (Representative Concentration Pathway: RCP 2.6 and RCP 8.5) to examine trends in shifting habitat suitability for each species. Maximum sea surface temperature was the main predictor variable, followed by minimum nitrate concentration, explaining both species' distributional shift across Subantarctic shorelines by the year 2050. Projection of the SDM for each species under altered environmental conditions to 30-40 years into the future resulted in a south poleward shift with a reduction in habitat range for both species. Such responses would threaten their persistence, local marine species richness, biodiversity, ecological function, and thereby, the commercial and ecosystem services provided by L. flavicans and G. skottsbergii in Subantarctic South America.
Keywords: species distribution models (sdm); marine habitat niches; warming temperatures; nutrient concentrations